The seipin complex Fld1/Ldb16 stabilizes ER–lipid droplet contact sites - Grippa, A; Buxó, L; Mora, G; Funaya, C; Idrissi, F-Z; Mancuso, F; Gomez, R; Muntanyà, J; Sabidó, E; Carvalho, P (Rockefeller University Press, 2015)
Lipid droplets (LDs) are storage organelles consisting of a neutral lipid core surrounded by a phospholipid monolayer and a set of LD-specific proteins. Most LD components are synthesized in the endoplasmic reticulum (ER), an organelle that is often physically connected with LDs. How LD identity is established while maintaining biochemical and physical connections with the ER is not known. Here, we show that the yeast seipin Fld1, in complex with the ER membrane protein Ldb16, prevents equilibration of ER and LD surface components by stabilizing the contact sites between the two organelles. In the absence of the Fld1/Ldb16 complex, assembly of LDs results in phospholipid packing defects leading to aberrant distribution of lipid-binding proteins and abnormal LDs. We propose that the Fld1/Ldb16 complex facilitates the establishment of LD identity by acting as a diffusion barrier at the ER-LD contact sites.